Landasan ontologi dan aksiologi ilmu - Atmaranti, Naysalwa Dwi (Maliki Interdisciplinary Journal, 2025)
This article discusses two main foundations in the philosophy of science, namely the ontological and axiological foundations of science. Ontology as a study of the nature of reality is the basis for determining formal and material objects in scientific activities. Meanwhile, the axiology of science discusses values, goals and ethics in the process and application of science. This study highlights how perceptions of reality (ontology) influence the way humans construct values, and how values (axiology) influence the direction and ethical responsibility in the application of science. This article concludes that a complete understanding of the ontological and axiological aspects is essential to avoid reducing science to merely a technical instrument, and to direct science towards human welfare and the sustainability of life.